Inhibitory control of threat remembering in PTSD. Issue 10 (26th November 2019) - Tudorache, Andrei-Cristian; El-Hage, Wissam; Tapia, Géraldine; Goutaudier, Nelly; Kalenzaga, Sandrine; Bouazzaoui, Badiâa; Jaafari, Nemat; Clarys, David
ABSTRACT: Intrusive traumatic recollections suggest an inability in Posttraumatic Stress Disorder (PTSD) to control and notably to inhibit memories for trauma-related information. Supported by inhibitory deficits found on experimental settings in PTSD, memory functioning and memory biases in the disorder were usually explained through inhibitory and control deficits in the processing of trauma-related information. The present study aimed to directly assess this hypothesis by investigating memory control abilities for emotional information in PTSD. For this purpose, 34 patients diagnosed with PTSD were compared to 37 non-PTSD controls on an item-cued directed forgetting paradigm for emotional words combined with a Remember/Know recognition procedure. Results revealed enhanced amounts of Remember recognitions for trauma-related words in PTSD. Moreover, we replicated findings of memory control impairments in the disorder. However, such impairments only occurred for non-trauma-related words. Accordingly, it appeared that PTSD patients presented preserved memory control abilities for trauma-related words, at the expenses of other emotional valences. Surprisingly, PTSD patients presented a preserved ability to control and notably to inhibit their memory functioning for trauma-related material. In addition to potential theoretical and clinical relevance, these results are discussed in the light of resource reallocation hypotheses and vigilant-avoidant theories of information processing in PTSD.